TEKNIK PENCUCIAN ALAT MAKAN, PERSONAL HYGIENE TERHADAP KONTAMINASI BAKTERI PADA ALAT MAKAN - Marisdayana, Rara; Harahap, Putri Sahara; Yosefin, Hesty (Jurnal Endurance, 2017)
The food is a important thing in the human life, because the food have fungtion give the power or energy in body, build the new body tissues. Opportunity happenstance of food contamination can happen at every preparation food step. The human factor or food processor has a big important influence in food preparation because the food processor can displace bacterio of E.coli to food and than the instruments as plate is the one of the important factor that can motivate spreading if deases.This research was the quantitative with cross sectional design, that purpose to know relationship between personal hygiene and technique of washing plate toward contamination of bacteria on the plate that use by the food stall at Traditional Market of Angso Duo Jambi City. The technique of take sample with quota sampling as many as 30 food stalls and datum was tested by chi-sqaure test. The results of the analysis found no relationship between washing techniques and personal hygiene to the number of germs in the cutlery used by food vendors Angso Duo Market Jambi City with a value of 1,000 pp.